Synaptic Scaffolds, Ion Channels and Polyamines in Mouse Photoreceptor Synapses: Anatomy of a Signaling Complex - Vila, Alejandro; Shihabeddin, Eyad; Zhang, Zhijing; Santhanam, Abirami; Ribelayga, Christophe P.; O’Brien, John (Frontiers in Cellular Neuroscience, 2021)
Synaptic signaling complexes are held together by scaffold proteins, each of which is selectively capable of interacting with a number of other proteins. In previous studies of rabbit retina, we found Synapse-Associated Protein-102 (SAP102) and Channel Associated Protein of Synapse-110 (Chapsyn110) selectively localized in the tips of horizontal cell processes at contacts with rod and cone photoreceptors, along with several interacting ion channels. We have examined the equivalent suites of proteins in mouse retina and found similarities and differences. In the mouse retina we identified Chapsyn110 as the scaffold selectively localized in the tips of horizontal cells contacting photoreceptors, with Sap102 more diffusely present. As in rabbit, the inward rectifier potassium channel Kir2.1 was present with Chapsyn110 on the tips of horizontal cell dendrites within photoreceptor invaginations, where it could provide a hyperpolarization-activated current that could contribute to ephaptic signaling in the photoreceptor synapses. Pannexin 1 and Pannexin 2, thought to play a role in ephaptic and/or pH mediated signaling, were present in the outer plexiform layer, but likely not in the horizontal cells. Polyamines regulate many ion channels, and control the degree of rectification of Kir2.1 by imposing a voltage-dependent block. During the day polyamine immunolabeling was unexpectedly high in photoreceptor terminals compared to other areas of the retina. This content was significantly lower at night, when polyamine content was predominantly in Müller glia, indicating daily rhythms of polyamine content. Both rod and cone terminals displayed the same rhythm. While polyamine content was not prominent in horizontal cells, if polyamines are released, they may regulate the activity of Kir2.1 channels located in the tips of HCs. The rhythmic change in polyamine content of photoreceptor terminals suggests that a daily rhythm tunes the behavior of suites of ion channels within the photoreceptor synapses.